UI/UX Design Using the Design Thinking Approach for a Location-Based Attendance System at PT Agung Sumatera Development - Sianturi, Ayu Elisya Natama; Septia Angelika Gettin Daely; Andayani, Sri (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2026)
Digital transformation has accelerated the adoption of technology-based attendance systems; however, manual attendance methods continue to exhibit limitations, including data manipulation and operational inefficiency. This study aims to design an optimal User Interface (UI) and User Experience (UX) for a location-based employee attendance system at PT Agung Sumatera Development using the Design Thinking approach up to the prototyping stage. The design process consisted of the empathize, define, ideate, and prototype phases, incorporating the MoSCoW prioritization framework Must-have, Should-have, Could-have, and Won't-have as well as the How Might We (HMW) technique to identify user needs and generate design solutions. Figma was employed as the primary design tool for developing the prototype. The proposed system integrates GPS-based location verification, real-time selfie authentication, and automatic watermark generation to enhance attendance accuracy and reliability. The resulting prototype features a simple workflow and intuitive navigation. A usability walkthrough involving five employees indicated that the design effectively met usability criteria in terms of ease of understanding and navigation clarity, achieving an average Task Completion Rate of 90%. Feedback regarding the readability of the location radius instruction was incorporated into the final design, resulting in improved user experience.